Implementation of the Muhadharah Program in Improving the Disciplined, Creative and Self-Confident Character of Students in Islamic Boarding Schools - Binti Rofii’ah; Katni Katni; Devid Dwi Erwahyudin; Muhamad Nabil Abidin; Kholid Muhtar Aziz; Achmad Basith Setiawan; Nila Agustin (Assyfa Journal of Islamic Studies, 2025)
In the midst of the rampant problems of indiscipline, stagnation and inferiority of some Indonesian students, but different Pesantren Salafiyah Hasan Munadi Ponorogo, developed the Muhadharah Program in improving the character of discipline, creativity and self-confidence of students. This study uses a qualitative descriptive approach research method, field research type. Data collection techniques use interviews, observations and documentation. Then the analysis technique through the stages of data codification, data presentation and drawing conclusions. The results of this study are 1) The Muhadharah Program is a superior program in this institution that must be followed by all students. Its implementation is carried out every Saturday, this program is carried out in turns by representatives of each class according to a predetermined schedule 2) The Muhadharah Program plays an important role in shaping the character of discipline and creativity and self-confidence of students. 3) supporting factors, namely, the involvement of competent educators, consistency and routine in implementing the program, support for a conducive environment, internal motivation of students and adequate supporting facilities. While the inhibiting factors are, lack of interest and motivation of students, dependence on monotonous teaching methods, time constraints, fear and shame, lack of learning oriented towards developing creativity and lack of facilities/resources. The purpose of this study is 1) To analyze the implementation of the Muhadharah program in fostering the character of discipline and creativity of students, 2) To analyze the role of Muhadharah in improving the character of discipline, creativity and confidence of students, 3) to analyze the supporting and inhibiting factors. This study recommends that the muhadharah program routinely and consistently can improve the character of discipline, creativity and confidence of students.